THE RELATIONSHIP OF SELF-CONCEPT AND RESILIENCE OF PROSPEROUS PRIVATE STUDENTS IN SMP NEGERI 4 LEMBAH GUMANTI KABUPATEN SOLOK REGENCY - Annisa Fitri; Firman Firman (Jurnal Neo Konseling, 2020)
Resilience and self-concept are very important for individuals (students) in facing economic difficulties they experience. By having good resilience and positive self-concept, individuals will be able to survive the difficulties that occur to them and be able to assess themselves properly in accordance with their physical, psychological and social conditions. Based on the phenomenon that is seen many students of SMP Negeri 4 Lembah Gumanti who have low resilience and self-concepts in dealing with the underprivileged conditions they experience. This study aims to see how the relationship of self-concept with the resilience of pre-Sumatra students at SMP Negeri 4 Lembah Gumanti. This research is a quantitative descriptive correlational type of research. The sample of this research was 44 students from grade VIII and IX students using total sampling technique (saturated sample). This study uses a questionnaire prepared using a Likert scale model of self-concept and resilience. Then the data were analyzed using descriptive and correlational analysis techniques using the moment prodact formula with the help of SPSS Version 26 for Windows. Based on the results of data processing that has been done shows that the self-concept with resilience of pre-prosperous students in SMP Negeri 4 Lembah Gumanti is positive and significant (r count > r table, significance 0.01).